Rancangan Conveyor Pemilah Benda Logam Yang Mengandung Magnet Neodymium Dan Non-Logam Berbasis Mikrokontroler - Andrianto Andrianto; Rummi Santi Rama Sirait (FAKULTAS TEKNIK UNIVERSITAS BUDI LUHUR, 2020)
In this study, an object control system was designed to separate metal objects containing neodymium and non-metallic magnets to different places using a gate. Which is controlled by the arduino mega2560. In the design of this study using a conveyor belt, a DC motor as the conveyor belt driver and there is 1 servo motor that is used to sort metal objects containing neodymium and non-metal magnets. The results obtained on this conveyor tool when the conveyor rotates then the inductive sensor detects metal objects containing neodymium or non-metallic magnets which are then read by the ultrasonic sensor 2 to read the object's whereabouts. So after that when the object detected by the inductive sensor reads metal containing a neodymium magnet, an inductive proximity sensor with logic 0, then the gate turns to the right and the object falls into a special metal place and when the object detected by the inductive proximity sensor reads non-metal then the inductive proximity sensor has logic. 1, then the gate turns left and the object falls into a special non-metal place. And when the ultrasonic sensor 2 does not detect the object for 10 seconds, the conveyor stops. Then if there is an object in front of the ultrasonic sensor 1, the conveyor is active again. From the tests conducted, it shows that the control system is in accordance with the original plan.